The older the wiser? Determinants of misbehaviour in team contests - Mario Lackner; Hendrik Sonnabend (Johannes Kepler University of Linz, Department of Economics, 2022)
We use data from top-level soccer to examine determinants of individual misbehaviour in team contests. Our estimates indicate a significant positive and non-linear relationship between a player's age and (relative) ability on the one hand and the tendency to misbehave on the other. These findings are consistent with Social Learning Theory in that the group of high-status players may has learned that the consequences of misconduct are low and manageable. Furthermore, we demonstrate that misbehaviour is costly to both the players and their teams.
Keywords: J32; J24; K42; L83; 330; misconduct; contests; status; soccer